Quality Strategy in Excellent Service System Management for Customer Satisfaction in Educational Institutions - Abidin, Zaenal; Hafidhah, Hafidhah; R. Madhakomala, R. Madhakomala; Rakhman, Nadine (Jurnal Edusci, 2025)
This study describes the quality strategy used to manage excellent service systems for customer satisfaction in educational institutions. This research uses a literature study method by observing various documents from books and journals. The literature study focuses on researching literature related to education quality strategies, excellent service of educational institutions, and educational customer satisfaction both internally and externally. Data collection is carried out by collecting literature data, reading, recording, and managing research results objectively, systematically, analytically, and critically by looking at the year of publication and the most up-to-date research. The results of this study show that the quality of educational institutions is the responsibility of all elements of the school. Quality Strategy The management of an excellent service system depends on the concept of quality management initiated, the excellent service provided by educational institutions to customers, and the orientation to what customers need. The concepts of quality management, excellent service, and customer satisfaction are three crucial components that must be possessed by educational institutions in order to produce a quality strategy for excellent service in educational institutions.